Perbedaan Hasil Belajar Antara Model Pembelajaran Kooperatif Tipe Team Assisted Individualization dengan Model Pembelajaran Konvensional Plus pada Mata Pelajaran Statika - Eka Wulandari; Daryati Daryati (LPPM Universitas Negeri Jakarta, 2013)
The Objective of this study to get the empirical data result of learning between student getting model of study of co-operative of type of team assisted individualization with getting conventional study model of plus and to know there is do not it him difference of result of learning study of co-operative of type of team assisted individualization with the conventional study of plus to result learn the statics of at class of X Technique Draw the Building SMKN 26 Jakarta. Knowing the result of student learning which still does not fulfill KKM in Statika lesson, then model of study of co-operative of type of team assisted individualization, this method obliges the students to be more active in doing the assignment of Statika lesson which is in the form of making question by the student with the answers.The result of the research is found the differences in the results of learning statika between model of study of co-operative of type of compared to by better Team Assisted Individualization of Conventional study model of Plus to the students of class X of technical wood construction SMKN 26 Jakarta